ESP language teaching: a key to development in Guanacaste The English Teaching Case in the Tourist Major of the Universidad Nacional, Chorotega Regional Branch - Villanueva Monge, Lucía Svetlana (Revista Ensayos Pedagógicos, 2009)
The Tourist Industry has had a great development in the last ten tears in Costa Rica. This country has many special attractive destinations for foreigners that surpass a million and a half annually. The province of Guanacaste, one of the biggest and more visited of the country, is the perfect sample to illustrate the "Tourist Boom" inhabitants are experimenting today. Because of the multiple impacts the tourist industry has in different settings, but especially in the economy of the province, there is a need to prepare people better, day by day, to work in the industry, satisfying its high standards of quality. One of these requirements is the full command of the English language.